Searching for Signatures of Cold Climate Adaptation in TRPM8 Gene in Populations of East Asian Ancestry - Igoshin, Alexander V.; Gunbin, Konstantin V.; Yudin, Nikolay S.; Voevoda, Mikhail I. (Frontiers in Genetics, 2019)
Dispersal of Homo sapiens across the globe during the last 200,000 years was accompanied by adaptation to local climatic conditions, with severe winter temperatures being probably one of the most significant selective forces. The TRPM8 gene codes for a cold-sensing ion channel and adaptation to low temperatures is the major determinant of its molecular evolution. Here, our aim was to search for signatures of cold climate adaptation in TRPM8 gene using a combined dataset of 19 populations of East Asian ancestry from the 1000 Genomes and Human Genome Diversity Project. As a result, out of a total of 60 markers under study, none showed significant association with the average winter temperatures at the locations of the studied populations considering the multiple testing threshold. This might suggest that the principal mode of TRPM8 evolution may be different from widespread models, where adaptive alleles are additive, dominant or recessive, at least in populations with the predominant East Asian component. For example, evolution by means of selectively preferable epistatic interactions among amino acids may have taken place. Despite the lack of strong signals of association, however, a very promising SNP was found. The SNP rs7577262 is considered the best candidate based on its allelic correlations with winter temperatures, signatures of selective sweep and physiological evidences. The second top SNP, rs17862920, may participate in adaptation as well. Additionally, to assist in interpreting the nominal associations the other markers reached, we performed SNP prioritization based on functional evidences found in literature and on evolutionary conservativeness.